2012
DOI: 10.1111/j.1365-2265.2011.04229.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of activated vitamin D on insulin resistance in nondiabetic chronic kidney disease patients

Abstract: Background Although vitamin D deficiency has been associated with increased insulin resistance, a causal link has not been established. Interpreting the relationship has been confounded by a close correlation between vitamin D deficiency and obesity. The current clinical approach of assessing endogenous 25-hydroxyvitamin D (25(OH)D) concentrations in patients with Chronic Kidney Disease(CKD), and independently administering activated vitamin D(AD), allows a unique opportunity to clarify cause and effect in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“… Forest plot for non-diabetic subject studies showing the correlation between status of vitamin D and fasting plasma insulin. The random effect model was used for the determination of correlation and 95% CI [ 19 , 20 , 57 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 ]. …”
Section: Figurementioning
confidence: 99%
“… Forest plot for non-diabetic subject studies showing the correlation between status of vitamin D and fasting plasma insulin. The random effect model was used for the determination of correlation and 95% CI [ 19 , 20 , 57 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 ]. …”
Section: Figurementioning
confidence: 99%
“…In 1,25(OH)2D deficient animals, intravenous 1.25(OH)2D administration improves glucose intolerance and induces insulin releasing from beta cells of pancreas in response to a glucose challenge (46). In a study involving 120 non-diabetic CKD patients, obese patients treated with 1,25(OH)2D had similar insulin concentrations compared to non-obese patients, whereas untreated obese patients had a higher insulin concentration (47). In our study, obese/overweight patients carrying FokI homozygous mutant TT genotype had higher glucose concentrations compared to those having CC and CT genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Some short-term studies with vitamin D supplementation in dialysis patients have shown increased insulin sensitivity and secretion (reviewed in [72]). A cross-sectional study of 120 non-diabetic CKD patients found that insulin levels were decreased in patients treated with activated vitamin D [74]. A cross-sectional study of 120 non-diabetic CKD patients found that insulin levels were decreased in patients treated with activated vitamin D [74].…”
Section: Insulin Resistancementioning
confidence: 99%